Enhancing essential oil yields from citronella (Cymbopogon winterianus) and Rosemary (salvia rosmarinus): An ultrasonication-assisted extraction approach using Response Surface Methodology - Karimah, Qosrul; Darmawan, Dhea Afrisa; Naufal, Widyan Muhammad; Putri, Denis Octareta Amelia; Syakirina, Dina; Carolina, Diah Fitri; Venny; Hapsari, Pinka Zuhdiana; Rahmaniar, Widya; Pradita, Agung Lucky; Firdaus, Maulidan (Separation science and technology, 2025)
This study aims to optimize essential oil (EO) yields through Ultrasonication-Assisted Extraction-Hydrodistillation (UAE-HD), focusing on Cymbopogon winterianus Jowitt ex Bor and Salvia rosmarinus ;(L.) Spenn. The UAE stage was optimized using Response Surface Methodology (RSM) with Box-Behnken Design (BBD). The independent variables i.e. volume of solvent, sonication temperature, and sonication duration were optimized against its yield in 15 designs. The optimum condition via the quadratic model was validated through ANOVA and the optimum results were achieved at 50°C with sonication for 20 minutes in 250 mL of distilled water. The EO component of both materials, either by UAE-HD or HD conventional, was analyzed using Gas Chromatography-Mass Spectroscopy (GC-MS). The main components of C. winterianus EO were citronella (36.27 %), geranial (29.75 %), and β-citronellol (18.41 %), while S. rosmarinus EO contained 1.8-cineole (23.06 %), α-pinene (17.50 %), neral (13.03 %), and verbenone (8.86 %). Leaf morphology differences were analyzed using Scanning Electron Microscopy (SEM), revealing that ultrasonication caused damage to the secretory glands, thereby accelerating the release of volatile components. This finding demonstrates the practicality of the proposed method for achieving higher EO yields.